An unusual cause of eyeball rupture: a case report - Darmawan, Handy (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Eyeball rupture due to ocular trauma is a major public health problem with a high global incidence. In contrast, non-trauma case of spontaneous eyeball rupture is extremely rare and is never been reported in Indonesia. In this report, we present a patient with spontaneous right eyeball rupture due to acute glaucoma secondary to hyper mature cataract. Although eyeball rupture in both trauma and non-trauma cases have the same poor outcome, non-trauma case of spontaneous eyeball rupture is preventable. Therefore, proper management and evaluation of the patients with cataract and glaucoma are necessary to avoid this rare and devastating outcome.